INTERNALISASI PENDIDIKAN INKLUSI DALAM PEMBINAAN MODERASI BERAGAMA MELALUI BELAJAR DI KELAS - Nuraini Nuraini (CV. ADIBA AISHA AMIRA, 2026)
Learning activities in classes with diverse students, where there are students with special needs, challenge teachers to pay more attention and fulfill all students, and develop learning through internalizing the values of Islamic Religious Education learning between training students in developing attitudes since elementary school with elements of activities. in class with a commitment to nationality, tolerance, non-violence, and accommodating to local culture. Teachers get used to stimulating students by showing honest, disciplined, responsible, caring, mutual cooperation, cooperation, tolerance, peace, polite, responsive and proactive behavior as part of the solution to various problems in interacting effectively with the social and natural environment and placing self as a reflection of the nation in various world relationships.